The relationship between self-regulated learning, mindful agency, and psychological resilience in Chinese master of nursing specialists: A cross-sectional study - Yang, Rui; Gao, YuFang; Ji, ZiTong (Frontiers in Psychology, 2023)
Background Self-regulated learning helps to improve academic performance and is an important strategy for the sustainable development of Master of Nursing Specialists. Consequently, it is relevant to identify the factors that affect self-regulated learning and analyze the correlation between them. Objective This study examined the status quo of self-regulated learning, the relationship between self-regulated learning, mindful agency, and psychological resilience, and explored whether mindful agency and psychological resilience influence self-regulation learning. Methods Chinese Master of Nursing Specialists were recruited to participate in an online survey from March to November 2022. Self-regulated learning, mindful agency, and psychological resilience were measured using three questionnaires, including the Self-Regulated Learning Scale for Clinical Nursing Practice Scale (SRLS-CNP), the Mindful Agency Scale, and the 10-item Connor-Davidson Resilience Scale (CD-RISC-10). The data were processed and analyzed using SPSS26.0. The statistical methods included descriptive statistics, Pearson’s correlation analyses, and multiple linear regression. Results Self-regulated learning of Chinese Master of Nursing Specialists was medium level (59.24±9.33 scores). Mindful agency and psychological resilience were positively correlated with self-regulated learning (P＜0.01) and important predictors of self-regulated learning of Master of Nursing Specialists, explaining 44.6% of the variation. Conclusions Mindful agency and psychological resilience affected the self-regulated learning level of Master of Nursing Specialists in clinical practice. These results will enable clinical educators to pay more attention to the personal psychological factors of Master of Nursing Specialists to improve their self-regulated learning ability through mindful agency and psychological resilience.